ChemInform Abstract: The Cinchona Primary Amine‐Catalyzed Asymmetric Epoxidation and Hydroperoxidation of α, β‐Unsaturated Carbonyl Compounds with Hydrogen Peroxide. Issue 42 (1st October 2013) - Lifchits, Olga; Mahlau, Manuel; Reisinger, Corinna M.; Lee, Anna; Fares, Christophe; Polyak, Iakov; Gopakumar, Gopinadhanpillai; Thiel, Walter; List, Benjamin
Abstract A highly enantioselective Weitz—Scheffer‐type epoxidation and hydroperoxidation employing acyclic enones, 5—15‐membered cyclic enones, and α‐branched enals as substrates is presented.